2022
DOI: 10.4218/etrij.2021-0239
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the leaders and main conspirators of the attacks in terrorist networks

Abstract: This study proposes a novel method for identifying the primary conspirators involved in terrorist activities. To map the information related to terrorist activities, we gathered information from different sources of real cases involving terrorist attacks. We extracted useful information from available sources and then mapped them in the form of terrorist networks, and this mapping provided us with insights in these networks. Furthermore, we came up with a novel centrality measure for identifying the primary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Our previously published research on four real-world terrorist networks revealed the distinct social roles of individuals in terrorist organizations [38] and uncovered successfully some early signs of impending terrorist attacks [39]. The fusion of social network analysis and machine learning methods provides valuable insights into the structure, operation, and dynamics of terrorist networks [37,[40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previously published research on four real-world terrorist networks revealed the distinct social roles of individuals in terrorist organizations [38] and uncovered successfully some early signs of impending terrorist attacks [39]. The fusion of social network analysis and machine learning methods provides valuable insights into the structure, operation, and dynamics of terrorist networks [37,[40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 96%
“…The increasing use of social media requires new approaches for analyzing and identifying influential nodes in terrorist networks [35]. Understanding the role of social ties is vital for preventing possible future terrorist activities [36,37]. Our previously published research on four real-world terrorist networks revealed the distinct social roles of individuals in terrorist organizations [38] and uncovered successfully some early signs of impending terrorist attacks [39].…”
Section: Introductionmentioning
confidence: 99%